Environmental activism and the Internet : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Sociology at Massey University - White, Clem (Massey University, 1999)
Environmentalism is used as a case study to investigate the value of the Internet for activism, protest and social change. The effectiveness of the Internet for helping environmental groups to achieve their goals and the implications of this medium for the future of the environmental movement are explored. An online (Internet) survey of environmental groups who are currently using the Internet was conducted. Two hundred and forty four requests to take part were emailed to environmental groups, eight of which were returned with invalid email addresses. Over the course of a three month period 79 completed surveys were collected, giving a response rate of 33%. Other methods utilised include face-to-face, telephone and email interviews with environmental group representatives, content analysis of Internet sites and the construction of a database of online environmental groups. Secondary data is also drawn upon extensively. This thesis examines the Internet's role in helping environmentalists achieve more with limited resources, network across wide geographic distances and create new forms of collective action. The changing role of other media and the ways in which the Internet may be influencing the dynamics between environmental groups and their opponents are also explored. Difficulties with this mode of communication must also be acknowledged. The concentration of Internet use in already privileged sectors of society may mean that participants in mainstream environmentalism are likely to have access, but it may also mean that the medium holds less promise for emerging ecojustice groups. It is also true that computers and network infrastructures are major causes of environmental harm, so it may appear contradictory to use these to try to protect the environment. This research suggests that the Internet offers a great deal of opportunity for environmental groups, but it also supports elements of contemporary society that many environmentalists oppose - increased consumerism, unfettered globalisation and direct environmental harm by its very existence. Activists should approach the Internet with optimism but not complacency. Those who seek to preserve aspects of the medium that promote community and democracy should endeavour to advance an alternative construction of the medium to that which is prevalent in the mainstream media.
Keywords: Environmentalism; Computer network resources; Environmental protection; Citizen participation